Menggali Nilai-Nilai Maqashid Syariah pada Wisata Pantai Camplong Kabupaten Sampang : Studi Analisis Ushul Fiqh - Taufiqur Rahman; Holis Holis; Adiyono Adiyono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to examine the principles of maqashid sharia in the tourism industry of Camplong Beach, Sampang Regency. It is expected that maqashid sharia which has five main objectives, namely protection of religion, soul, mind, descendants, and property, will offer a moral and ethical basis for sharia-based tourism management. Camplong Beach has a lot of potential to uphold the values ​​of maqashid sharia as a developing tourist resort. By using field research techniques, interviews, and documentation, this study takes a qualitative approach. The conclusion of the study shows that a number of maqashid sharia values, including preserving the environment (hifz an-nasl), empowering the local economy (hifz al-mal), and educating and promoting religious values ​​to tourists (hifz ad-dtn), can be used to manage Camplong Beach tourism. Thus, it is expected that the application of the concept of maqashid sharia in tourism management will encourage sustainability and provide a wider positive influence on local residents and tourists. Thus, Camplong Beach can be an example of sharia tourism that is financially successful and in accordance with Islamic law.